Activities of the wintering party of the 34th Japanese Antarctic Research Expedition in 1993-1994 - Natsuo Sato (Nankyoku shiryo, 1999)
The wintering party of the 34th Japanese Antarctic Research Expedition (JARE-34), which consisted of 40 members including one foreign scientist, wintered at Syowa Station from February 1993 to January 1994. Observations at Syowa Station were conducted on various subjects such as meteorology, upper atmosphere physics, ionosphere, solid earth science and environmental science. A superconducting gravimeter was newly installed and the Earth's free oscillations were observed. The total ozone content reached a minimum value in October 1993. Intensive field activities in geology, geomagnetism, marine biology and glaciology were carried out in the coastal areas and inland plateau. The wintering period of JARE-34 was the 2nd year of the deep ice core drilling project at Dome Fuji Station. Several inland traverse parties were sent to the relay-point and Dome Fuji Station to transport fuel and construction materials. Nine members stayed at Dome Fuji Station for more than three months in the austral summer of 1993 to 1994 and constructed some buildings for ice drilling. The Syowa Station facilities were maintained very well through the efforts of the logistic members.